262 Pre-operative wait times in high risk endometrial cancer: do surgical delays impact patient survival?. (13th November 2020) - Nica, A; Sutradhar, R; Covens, A; Kupets, R; Vicus, D; Li, Q; Ferguson, S; Gien, LT
Abstract : Objectives: Practice guidelines advocating for the regionalization of endometrial cancer surgery to gynecologic oncologists (GO) practicing in designated gynecologic oncology centres were released by Cancer Care Ontario in June 2013. We sought to determine the impact this policy had on contemporary surgical wait times, and whether longer wait time to surgery is a predictor of survival in patients with high risk endometrial cancer. Study Methods: This was a retrospective cohort study, which included patients diagnosed with non-endometrioid high-risk endometrial cancer (serous, carcinosarcoma, clear cell, and undifferentiated) between 2003 and 2017. A cut point of January 2014 was chosen to allow 6 months for knowledge translation and define 2 regionalization periods. Results: We identified 3518 patients with high risk endometrial cancer. Patients who had surgery with a GO had a median surgical wait time from diagnosis to hysterectomy of 55 days compared to 59 days pre-regionalization (p=0.0002), and from first GO consultation to hysterectomy of 29 days compared to 32 days pre-regionalization (p=0.0006). Survival was worst for patients who had surgery within 14 days of diagnosis (HR death 1.94, 95%CI 1.48–2.54), indicating disease severity. Decreased survival occurred with surgical wait times of more than 45 days from the patient's first GO appointment (HR death 1.19, 95%CI 1.04–1.36). Conclusion: Regionalization of surgery for high risk endometrial cancer has not had a negative impact on surgical wait times. Impact on survival is seen with patients who have surgery more than 45 days after surgical consultation.